Improving Teacher Discipline Through The Implementation Of Reward And Punishment In Class Teaching Attendance At Sdn 007 Suka Damai, Singingi Hilir District, Kuantan Singingi Regency - Sriyanto Ramelan Sutoyo (STKIP Rokania Pasir Pangaraian, 2021)
research is look for an alternative solution of the problem as efforts to improve the discipline of teachers in attendance to teach in class through the implementation of reward and punishment. This research was carried out in three cycles, because from the results of research and data analysis, it turned out that in the third cycle , discipline teachers in attendance in classes on the process of learning to teach to rise and meet the indicators that have been set at 75%. From the results of research it , can be concluded that to improve the discipline of teachers in attendance in classes on the activities of learning to teach can be done with the implementation of reward and punishment to the teacher